Determining a threshold in effect of ocean acidification on crustose coralline algae (including a case study to teach at school) - Bradassi, Fulvia (Università degli studi di Trieste, 2012)
2010/2011 The recent and steady CO2 increase, mainly due to human activities, causes a shift in the chemical equilibrium of the carbonates dissolved in sea-water, which results in a lowering of pH level. This phenomenon, known as ocean acidification, interacts with many physiological processes, including, calcification due to biological factors. Plenty of consequences can affect both the ecosystem and the human society; the latter benefits from goods and services produced by the ecosystem itself, such as fishing, shoreline protection, landscape, tourist and recreational activities. It seems there isn’t much awareness of all of this. The study of the effect of acidification on coralline algae (Corallinales) is of primary importance for the comprehension of the consequences at ecosystem level, since the Corallinales represent one of the key groups in the formation of submerged habitats, but also because they’ve proven to be some of the most responsive to acidification. The question that was tried to answer is whether the calcareous algae can be resilient towards acidification and, if that is so, which is the threshold value beyond which that ability expires. In this analysis, particular attention has been paid to reproductive phases, that represent a de facto sensitive point in the life cycle. Il recente e costante aumento della CO2 dovuto principalmente alle attività antropiche provoca un’alterazione dell’equilibrio chimico dei carbonati disciolti nell’acqua marina, che si traduce in un abbassamento del pH. Questo fenomeno, noto come ocean acidification, interagisce con numerosi processi fisiologici fra cui, in primis, la calcificazione di origine biologica. Numerose potrebbero essere le conseguenze sugli ecosistemi, e quindi anche sulla società umana, che usufruisce di beni e servizi prodotti dagli ecosistemi stessi, come la pesca, la protezione della linea di costa, il paesaggio e le attività turistico - ricreative. Di tutto questo non sembra esserci in realtà grande consapevolezza. Lo studio degli effetti ...